Characteristics Of Communicative Distance In The Relationship Between Teachers And Students Of Schools - Ismatova N.K (Euro Asian Journal Publishing, 2024)
The article analyses the levels of relationships between teachers and students based on their recipient and communicative roles. As a result, the levels of communicative distance in the relationship between teachers and students were determined. After a certain experiment, a group of students with low levels of communicative distance in relationships with teachers was formed. After conducting psychological trainings, a repeated empirical experiment was carried out and the results were obtained to improve the relationship between teachers and students. The article provides a comparative analysis of empirical indicators of relationships between teachers and students before and after psychological trainings on communicative distances
Keywords: recipient; teacher; student